O ensino profissional no Plano Nacional de Educação: as questões da oferta, do atendimento e da formação profissional - Brandao, Carlos da Fonseca [UNESP] (My University, 2011)
The aim of this paper is to discuss the issues of supply, service and training put in the brazilian National Education Plan (Law No. 10.172/2001), whose term expired in January 2011. Since a new project of the National Education Plan for the next decade, is currently under discussion in Congress, believe to be of paramount importance to examine which goals that have been achieved, which were partially achieved and what have not yet been achieved, always aiming to better development of professional education in Brazil, we consider mode of teaching still undervalued in the context of public education policies in Brazil.

O objetivo do presente artigo é o de discutir as questões da oferta, do atendimento e da formação profissional postas pelo Plano Nacional de Educação (Lei n° 10.172/2001), cuja vigência expirou em janeiro de 2011. Visto que um novo projeto de Plano Nacional de Educação (PNE) para a próxima década, encontra-se atualmente em discussão no Congresso Nacional, entendemos ser de suma importância analisar quais os objetivos e metas que já foram alcançados, quais foram parcialmente alcançados e quais ainda não foram alcançados, sempre objetivando o melhor desenvolvimento da educação profissional no Brasil, modalidade de ensino que consideramos ainda pouco valorizada no contexto das políticas públicas de educação no Brasil.
The professional teaching in the national plan for education: issues about the supply, the service and the professional training
Keywords: Professional education; National Education Plan; Public policy education; Plano Nacional de Educação; Ensino Médio; Ensino Profissional